Pengaruh Profitabilitas, Free Cash Flow, dan Ukuran Perusahaan Pada Nilai Perusahaan - Widiastari, Putu Ayu; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 23 No 2 (2018)DO - 10.24843/EJA.2018.v23.i02.p06, 2018)
The company's goal is not only to gain profit, but also to shareholder prosperity through enhancing corporate value. Company value is reflected from its share price. This study aims to determine the effect of profitability, free cash flow, and firm size on the value of the company. This study was conducted on consumer goods companies listed on the Indonesia Stock Exchange during the period 2011-2015. The number of samples used are 24 companies with sampling method using non probability sampling method. Data collection method used is non participant observation. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis found that the profitability and size of the company have a positive influence on the value of the company. While free cash flow does not affect the value of the company.